Yohanes Indra Jurnal PPKn PERAN GURU PPKN DALAM MENGEMBANGKAN KARAKTER PANCASILA DALAM KEHIDUPAN DI SEKOLAH (Studi Kasus di SMA Negeri Colomadu pada Siswa Kelas Sebelas IPA 1 dan 2): PERAN GURU PPKN DALAM MENGEMBANGKAN KARAKTER PANCASILA DALAM KEHIDUPAN DI SEKOLAH (Studi Kasus di SMA Negeri Colomadu pada Siswa Kelas Sebelas IPA 1 dan 2) - Yohanes Indra Yohanes Indra; Sugiaryo Sugiaryo; Siti Supeni (Prodi PPkn Universitas Slamet Riyadi, 2022)
AbstractThis study aims to determine the role of Pancasila and Citizenship Education teachers indeveloping the Pancasila character for students, to find out the obstacles faced by CitizenshipEducation teachers, and to find out the strategies used by teachers in developing Pancasilacharacter in Science 1 and 2 class students of SMA Negeri Colomadu. This research is aqualitative research using a descriptive approach. The subject of this research is the PPKn 11grade science 1 and 2 graders of SMAN Colomadu. The object is the teacher's role indeveloping the character of Pancasila values and their implications in school life. Collectingdata through interviews, observation and documentation. The data analysis technique used isa qualitative descriptive analysis technique with an interactive model.The results of the study conclude that the role of Civics teachers at SMA Negeri Colomadu isas role models for students by applying behavior to each individual in instilling thedevelopment of Pancasila character, such as emphasizing honesty, noble character, wisdomand shared responsibility. The obstacle is that there are still some teachers who do notprovide examples of role models to their students, for example there are still teachers whoarrive late and the teacher has not been able to place themselves according to the charactervalues of their place and the last one is the development of a fast-paced and complex andmodern era, so that students experience deviations that result in juvenile delinquency. Thestrategy used is to apply the face-to-face lecture method and variation strategies in learningby exemplary in instilling Pancasila values in everyday life.Keywords: The role of PPKn teachers, Pancasila character.